Rancang Bangun Tempat Sampah Terintegrasi d engan Dinding Transparan d alam Upaya Pemilahan Sampah - Made Ari Witarsa; Ida Ayu Gede Bintang Madrini; I Putu Gede Budisanjaya (Program Studi Teknik Pertanian dan Biosistem, Fakultas Teknologi Pertanian, Universitas Udayana, Badung, Bali, Indonesia, 2023)
Waste segregation is important for improving the environment's health, and society also protects natural resources. The purpose of this study is to design an integrated and transparent trash bin to sort waste and test the feasibility and effectiveness of the design. The design of the trash bin is based on functional and structural design. Questionnaire data were obtained from testing the feasibility and effectiveness design. The black color is used in this trash bin because it is identic to hummus. The frame construction is declared safe because it can support a garbage load of 75 kg per unit with frame tensile stress (σ) of 57.119 N/mm2, smaller than the allowable stress (σ) of the 88.630 N/mm2. The integrated and transparent trash dimensions were 120x40x138 cm, with three acrylic units, namely organic, inorganic, and glass bottles and cans. Additional parts are the cover of the three transparent units, the roof, the wheels, and the plastic waste storage section. This trash bin was declared feasible because the test results stated that they agreed with the design results score of 74% - 91%. The results of testing the effectiveness of the integrated and transparent design of the trash bin, that is, most of the respondents were categorized as fast and appropriate in sorting waste